Interpreting A Dream In The Movie “When It Stops Here” With Psychoanalysis Theory Using The Symbolic Method By Freud (Cinematology: Journal Anthology of Film and Television Studies, 2024)
Film is a visual art form that combines moving images, sound and narration to convey a story or message to the audience, it can also act as a medium to deepen understanding of the mental state possessed by humans. In interpreting dreams according to Freud, it can be done through two methods, namely Dream Interpretation using one of Freud’s methods, namely the symbolic method, which means interpreting dreams as a whole with dreams that are thought about repeatedly, it can affect human memory about the meaning of these dreams carried out using qualitative methods through an analytical descriptive approach. In the movie Ketika Berhenti Disini, in every scene where Dita wears glasses given by Ed, glasses are interpreted as clarity in seeing. A sign that there will be clarity in seeing, if in the context of this film is Ed's existence in the form of AI. which if you remove the food will disappear, is interpreted as a blur in the glasses because Ed cannot be seen again. The unity of a complete dream that is felt or done repeatedly can have an impact on the thinking of the brain itself in understanding a dream and seeing the dream. Every human being has fears, deep fears and also sadness that every human being always has. All of these things will be healed with good support from the environment and people around.